Impact of longer term phosphorus control on cardiovascular mortality in hemodialysis patients using an area under the curve approach: results from the DOPPS. Issue 10 (29th June 2020) - Lopes, Marcelo Barreto; Karaboyas, Angelo; Bieber, Brian; Pisoni, Ronald L; Walpen, Sebastian; Fukagawa, Masafumi; Christensson, Anders; Evenepoel, Pieter; Pegoraro, Marisa; Robinson, Bruce M; Pecoits-Filho, Roberto
Abstract: Background: Serial assessment of phosphorus is currently recommended by the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines, but its additional value versus a single measurement is uncertain. Methods: We studied data from 17 414 HD patients in the Dialysis Outcomes and Practice Patterns Study, a prospective cohort study, and calculated the area under the curve (AUC) by multiplying the time spent with serum phosphorus >4.5 mg/dL over a 6-month run-in period by the extent to which this threshold was exceeded. We estimated the association between the monthly average AUC and cardiovascular (CV) mortality using Cox regression. We formally assessed whether AUC was a better predictor of CV mortality than other measures of phosphorus control according to the Akaike information criterion. Results: Compared with the reference group of AUC = 0, the adjusted hazard ratio (HR) of CV mortality was 1.12 [95% confidence interval (CI) 0.90–1.40] for AUC > 0–0.5, 1.26 (95% CI 0.99–1.62) for AUC > 0.5–1, 1.44 (95% CI 1.11–1.86) for AUC > 1–2 and 2.03 (95% CI 1.53–2.69) for AUC > 2. The AUC was predictive of CV mortality within strata of the most recent phosphorus level and had a better model fit than other serial measures of phosphorus control (mean phosphorus, months out of target). Conclusions: We conclude that worse phosphorus control over a 6-month period was strongly associated with CV mortality. The more phosphorus values do not exceed 4.5 mg/dL the better is survival. Phosphorus AUC is a better predictor of CV death than the single most recent phosphorus level, supporting with real-world data KDIGO's recommendation of serial assessment of phosphorus to guide clinical decisions.